Sweden : 2005 Article IV Consultation - Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report, 2005)
Sweden's 2005 Article IV Consultation reports that strong productivity gains, wage moderation, and falling nonenergy import prices contributed to reducing inflation, and creating room for aggressive monetary easing. Export growth has been led by a strong recovery in the telecommunications and automobile sectors, and, combined with rising capacity utilization and record low interest rates, helped sustain a revival of business investment after a three-year slump. Rising disposable incomes and an expansionary monetary stance helped support consumer confidence.